Palace of the drowned [large type] - Mangan, Christine (Christine Rose) (Wheeler large print hardcover series., 2021)
"It's 1966 and Frankie Croy retreats to her friend's vacant palazzo in Venice. Years have passed since the initial success of Frankie's debut novel and she has spent her career trying to live up to the expectations. Now, after a particularly scathing review of her most recent work, alongside a very public breakdown, she needs to recharge and get re-inspired. Then Gilly appears. A precocious young admirer eager to make friends, Gilly seems determined to insinuate herself into Frankie's solitary life. But there's something about the young woman that gives Frankie pause. How much of what Gilly tells her is the truth? As a series of lies and revelations emerge, the lives of these two women will be tragically altered as the catastrophic 1966 flooding of Venice ravages the city. Suspenseful and transporting, Christine Mangan's Palace of the Drowned brings the mystery of Venice to life while delivering a twisted tale of ambition and human nature"--